Socialization of the Village SDGs Program in Realizing Villages Without Hunger and Poverty - Amruddin, Amruddin; Ekobelawati, Fransiska; Kusnadi, Iwan Henri; Natsir, Imron; Chatun, Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
Village SDGs (Sustainable Development Goals) are an integrated effort to create a village without poverty and hunger, a village with an even economic growth, a village that cares about health, a village that cares about the environment, a village that cares about education, a women-friendly village, a networked village, and a culturally responsive village to accelerate the achievement of the Development Goals Sustainable. Village SDGs is a sustainable development role that will be included in the priority program for using Village Funds in 2021. Every village in Indonesia has started planning and implementing Village SDGs, including Siturate Village in Cikande District, Serang Regency, Banten. In its implementation, village governments still experience many obstacles, such as collecting village community data, technical data updating and how to disseminate village information. This obstacle occurs due to the village government's lack of understanding regarding the implementation of village SDGs and also the absence of routine assistance from the Village Community Empowerment Service. Therefore, the aim of this community service is to help overcome the problems faced by residents in determining the direction of village development based on Village SDGs so that they can create a developed village without poverty in Situterate Village in Cikande District, Serang Regency, Banten. To obtain the data used were observation, literature review and educational methods. The educational methods used include socialization and counseling as a means of transferring knowledge and education for community empowerment. As a form of thought from the author, several efforts and breakthroughs have been offered, namely: 1.) Increasing participants' understanding and knowledge of the village SDGs program along with the implementation of targets in the village SDGs in determining the direction of more advanced village development, 2.) The role of village government that can using the Village SDGs application in order to update village data to make it better and more advanced so that it can create villages without hunger and poverty